Сучасне фотомистецтво України: соціальний досвід та нові художні рішення - Міщенко, Марина Миколаївна (НТУ "ХПІ", 2014)
Стаття присвячена дослідженню розвитку фотомистецтва в Україні на сучасному етапі, огляду основних фотопроектів в ряду визначних арт-практик в нашій державі, виявленню основних напрямків роботи українських фотомитців. Актуальність дослідження зумовлена потребою осмислення фотомистецтва в історії культури України, а також визначення місця української фотографії в світовому фотопроцесі. Показано, що сьогодні фотографія є повноправною учасницею мистецького процесу, існуючи як окремо, так і будучи частиною перфомансів, інсталляцій, хеппенінгів, арт-об’єктів та ін.

The paper studies the development of photography in Ukraine at present, exploring major photo projects and revealing main trends of Ukrainian photographers’ activities. The relevance of the study is due to the need for understanding of photography in the cultural history of Ukraine as well as the determination of the role of Ukrainian photography in the world photo processes. Nowadays photography is a cultural phenomenon that obtains certain characteristics: it has its own practices and technologies, photography creates specific images using photo devices, and moreover it is a way of communication and concentration of social experience. The peculiarity of photography is that it is always involved in social experience, whether it is amateur or professional photography, mass media or fine art one. Ukrainian photography during the period of independence could be considered exactly in terms of social experience. According to this approach the important thing is not only an actual image of reality in a photo or the message that an author intends to convey, but also the historical, social and cultural conditions accompanying its creation. Identifying this context is relevant both for the Ukrainian photographer and for the reception of Ukrainian photography in general.
Contemporary Photography of Ukraine: social experience and new artistic solutions
Keywords: фотомистецтво; історія фотографії; фотопроект; арт-практика; візуальне мистецтво; photography; history of photography; photo project; art practice; visual arts